Implementation of the Student Centered Learning Approach in Improving English Learning Outcomes - Najib, Maulana Iqbal Lubabun; Manan, Nanan Abdul; Casnan, Casnan; Hermwan, Hermawan; Hadiana, Oman (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2024)
This research aims to investigate the implementation of the Student Centered Learning approach in improving students' English learning outcomes. The research method used is a quantitative experimental method with a One Group Pretest-Posttest Design. The research sample consisted of 20 class II mattayom students at Eakkapapsasanawich Islamic School Krabi Thailand. The research was conducted for one month by applying the Student Centered Learning approach in English language learning. Data collection was carried out through pretest and posttest with written tests. The result show that implementing the student center learning approach is more effective in improving learning outcomes in learning English integers for class II Mattayom students compared to applying conventional learning. Based on the results of the t test analysis using the pretest and posttest data normality test and the results are known that pretest 0.19 > 0.05 and posttest 0.200 > 0.05 can be accepted and normally distributed, which means there are differences in the positive influence and effectiveness of implementing the student center learning approach applied in the experimental class.